A bibliometric analysis of college students' entrepreneurial intention from 2000 to 2020: Research trends and hotspots - Tingting, Gao; Jiangfeng, Yang; Yinghua, Ye (Frontiers in Psychology, 2022)
Based on 454 articles related to college students’ entrepreneurial intention in the Web of Science Core Collection, this study explores the hotspots and trends of international research on college students' entrepreneurial intention by using a combination of coding and bibliometric analysis. The research hotspots are as follows: the theory of planned behavior is the main theoretical basis of these studies; entrepreneurship education is a more important predictor of college students' entrepreneurial intention, and this relationship is regulated by multiple variables; personal traits, several types of capital theories, social entrepreneurial intention, and quantitative research methods are also common. The research fronts include the following: systematic review of the field, continuous attention to the theory of planned behavior, and in-depth exploration of the differentiated influence of entrepreneurial education on entrepreneurial intention. Finally, we proposed research thinking and prospects related to research on undergraduates' entrepreneurial intention and entrepreneurial education.